Amyloidoma, an Unusual Cause of Fracture - Frank Verhoeven; Clément Prati; Daniel Wendling (Case Reports in Rheumatology)
We report a case of a spontaneous hip fracture in a context of dysglobulinemia. The bone histologic examination found amyloidoma. Amyloidoma is an overload pathology and an unusual cause of fracture. In most of the cases, it is associated with myeloma and the difference between bone invasion of myeloma and amyloidoma in an osteolytic radiographic picture is not easy but is of importance because prognosis and treatment may be totally different. Thus, in the context of dysglobulinemia, one must keep in mind that spontaneous bone fracture may be due to amyloidoma with another prognosis.